2022
DOI: 10.1161/circulationaha.121.058542
|View full text |Cite|
|
Sign up to set email alerts
|

Coronary Artery and Cardiac Disease in Patients With Type 2 Myocardial Infarction: A Prospective Cohort Study

Abstract: Background: Type 2 myocardial infarction is caused by myocardial oxygen supply-demand imbalance, and its diagnosis is increasingly common with the advent of high-sensitivity cardiac troponin assays. Although this diagnosis is associated with poor outcomes, widespread uncertainty and confusion remain among clinicians as to how to investigate and manage this heterogeneous group of patients with type 2 myocardial infarction. Methods: In a prospective cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 44 publications
0
44
0
Order By: Relevance
“…Adverse remodeling occurs to a lower extent in this group of patients, as demonstrated by a study that showed that in more than half of the patients with a diagnosis of type 2 myocardial infarction, there was no imaging evidence of any functional consequences of myocardial infarction, such as a regional wall motion abnormality or scar formation. However, it is a known fact that these patients have a prognosis similar to those with an atherothrombotic MI, with a similar rate of future cardiovascular events [ 17 ].…”
Section: Pathophysiology Of Adverse Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse remodeling occurs to a lower extent in this group of patients, as demonstrated by a study that showed that in more than half of the patients with a diagnosis of type 2 myocardial infarction, there was no imaging evidence of any functional consequences of myocardial infarction, such as a regional wall motion abnormality or scar formation. However, it is a known fact that these patients have a prognosis similar to those with an atherothrombotic MI, with a similar rate of future cardiovascular events [ 17 ].…”
Section: Pathophysiology Of Adverse Remodelingmentioning
confidence: 99%
“…Furthermore, LGE can identify microvascular obstruction after MI, by visualizing the no-reflow phenomenon [ 22 ]. Finally, CMR is extremely useful in evaluating the etiology of MINOCA, and novel CMR techniques will bring further insight into ventricular remodeling after MI [ 17 , 22 , 107 , 108 ].…”
Section: Imaging Techniques Of Adverse Remodelingmentioning
confidence: 99%
“…Bularga et al 5 state that their “novel observations provide useful insights that will encourage clinicians to consider imaging in these patients.” I agree. However, they also state “If cardiac imaging does not identify coronary artery disease or infarction, then it is unlikely the patient will benefit from therapies targeting coronary atherosclerosis.…”
Section: Ischemic Threshold Subjective and Objective Evidence Of Isch...mentioning
confidence: 99%
“…Bularga et al 5 state that their "novel observations provide useful insights that will encourage clinicians to consider imaging in these patients. " I agree.…”
Section: Ischemic Threshold Subjective and Objective Evidence Of Isch...mentioning
confidence: 99%
See 1 more Smart Citation